Virtual Reality as Non-Pharmacological Therapy for Managing Chemotherapy Complications in Cancer: A Systematic Review - Hidayat, Arip; Murtiningsih, Murtiningsih; Ganefianty, Amelia (Jurnal Pendidikan Keperawatan Indonesia, 2024)
Introduction: Cancer patients undergoing chemotherapy often experience physical and psychological side effects from treatment. Virtual Reality (VR) is emerging as a non-pharmacological therapy to alleviate these complaints. Objective: This systematic review evaluates the impact of VR interventions on physical and psychological complaints in cancer patients undergoing chemotherapy. Methods: A systematic review was conducted using the PRISMA guidelines. Articles were sourced from ProQuest, Cochrane Library, and PubMed, limited to studies published between 2013 and 2023, in English, and containing original research findings. Results: Ten studies were reviewed, revealing that VR interventions reduce depression, pain, and anxiety, enhance comfort, and improve patients’ quality of life. Conclusion: VR technology offers a promising non-pharmacological intervention for managing chemotherapy-related side effects. It supports reducing anxiety, depression, pain, and fatigue while enhancing comfort and quality of life for cancer patients undergoing treatment. Further research is recommended to optimize VR applications in healthcare.